As expressoes idiomaticas: um processo de recriacao - Gonzales, Margareth Vasques Falleiros (2006)
This work has as its main subject the idiomatic expressions. On the evidence of the low number of Brazilian works and researches found in the matter of Phraseology, the restriction of knowledge to academics means, the fact that this phraseological groups don t appear in dictionaries nor in didactic manuals, being relegated to an inferior level in the extent of linguistic studies, we try to verify in this text, that idiomatic expressions are recreated in every new communicative situation, fulfilling the needs of the speaker. Emphasizing the creativity and vitality attributed to this sort of expression. Furthermore, we signalize that these idiotism hold in its within cultural hidden characteristics that connect themselves to its society and its spoken language. Grounding the work in previous works of Lakoff & Johnson (2002) for the metaphorical thought, of Biderman (2001) for the Lexicology, and in the Social Representations theory of Minayo (1995), we have developed a research confirming that cognitive operations are responsible for the appearance of idiomatic expressions in a language, as for its recreation. At the stage of analyzing the corpus, we have elected the book Grande Sertão:Veredas, by Guimarães Rosa, since the author uses this type of expression in a very sui generis way. By the means of comparative analysis, we have verified that the appearance process consists in total or partial substitution of terms, in the addition of suffixes and in grammatical classes changes for the consolidated expression terms. Throughout this analysis, we have ascertained that a recreated expression brings an original meaning, intense and amplified, delegating to Rosa s diction a unique freshness and flushness, that perpetuates it. Hence, we have proposed ourselves to expose that the non-(re)cognizing of idiomatic expressions in linguistic studies applies in not knowing other mental cognitive processes, essential for the understanding of the origin of the language, its functioning and its lexical uses.